Can APOE and MTHFR polymorphisms have an influence on the severity of cardiovascular manifestations in Italian Pseudoxanthoma elasticum affected patients? - Federica Boraldi; Sonia Costa; Claudio Rabacchi; Miriam Ciani; Olivier Vanakker; Daniela Quaglino (Molecular Genetics and Metabolism Reports, 2014)
Background: The clinical phenotype of Pseudoxanthoma elasticum (PXE) affected patients, although progressive with age, is very heterogeneous, even in the presence of identical ABCC6 mutations, thus suggesting the occurrence of modifier genes. Beside typical skin manifestations, the cardiovascular (CV) system, and especially the peripheral vasculature, is frequently and prematurely compromised. Methods and results: A cohort of 119 Italian PXE patients has been characterized for apolipoprotein E (APOE) and methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms by PCR. The severity of the clinical phenotype has been quantified according to the Phenodex PXE International score system. Statistical analysis (chi2 test, odd ratio, regression analysis, analysis of variance) were done by GraphPad. Data demonstrate that the frequency of APOE alleles is similar in PXE patients and in healthy subjects and that the allelic variant E2 confers a protection against the age-related increase of CV manifestations. By contrast, PXE patients are characterized by high frequency of the MTHFR-T677T polymorphism. With age, CV manifestations in T677T, but also in C677T, patients are more severe than those associated with the C677C genotype. Interestingly, compound heterozygosity for C677T and A1298C polymorphisms is present in 70% of PXE patients. Conclusions: PXE patients may be screened for these polymorphisms in order to support clinicians for a better management of disease-associated CV complications.